The Apinayé indigenous people and access to the Rural Education degree of the Federal University of Tocantins: Some reflections - Anderson Brasil; Cícero da Silva (Arizona State University, 2020)
This paper aims to discuss the access of the Apinayé indigenous people to the Rural Education Degree: Codes and Languages - Arts and Music, at the Federal University of Tocantins (UFT), Tocantinópolis campus, state of Tocantins, Brazil, as well as to dialogue with some contemporary theorists (Brandão, 1983; Haesbaert, 2016; Lévi-Strauss, 1973; Nimuendajú, 1956; Santos, 1999)  about socio-cultural diversity in the State of Tocantins. For that, the research addresses aspects of selection processes, didactic-pedagogical practices, language and affirmative policy programs that (do not) favor the access and inclusion/permanence of these students in the University. The research is of a bibliographical and exploratory nature, with a qualitative-interpretative approach. Since its first selection process in 2014, this graduation course annually welcomes incoming Apinayé indigenous students. The research results show that, although UFT uses different affirmative actions such as specific programs to welcome and support indigenous students and the didactic-pedagogical activities implemented in the classroom in the Degree in Rural Education have their specificities focused on the formation of the people of the countryside, all this has not been enough to guarantee the inclusion/permanence of the indigenous people in this undergraduate course. The largest barriers faced by Apinayé students have been the Portuguese language and the epistemology of academia.